2009
DOI: 10.1039/b901711a
|View full text |Cite
|
Sign up to set email alerts
|

Neutral and cationic main group element cages of germanium(ii) with pyrazolyl ligands: solid state structures, DFT calculations and advanced solution NMR investigations

Abstract: Two equivalents of 3,5-bis(trifluoromethyl)pyrazole or 5-methyl-3-(trifluoromethyl)pyrazole react with [Ge{N(SiMe(3))(2)}(2)] to give dimeric homoleptic germanium(ii) compounds [{Ge(3,5-RR'pz)(2)}(2)] (R = R' = CF(3) (1); R = Me, R' = CF(3) (2)), which provide cationic triply pz-bridged cages of the general formula [Ge(mu(2)-3,5-RR'pz)(3)Ge](+)[OTf](-) (R = R' = CF(3) (3); R = Me, R' = CF(3) (4)) upon treatment with one equivalent of triflic acid (HOTf, HSO(3)CF(3)). The compounds were studied using the pulsed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…We speculated that the intermetallic communication in these polynuclear scaffolds might be raised by increasing the overall orbital overlap of the constituents. Based on our experience with divalent Group 14 element compounds containing N ‐ligands,– and ligands based on heavier Group 14 elements, we thought to achieve this goal by substituting the carbene C atom in FcDAC with a heavier, divalent Group 14 element, that is, by a donor atom featuring much larger and more diffuse valence orbitals, in particular the π‐acceptor orbital . Therefore, we became interested in exploring the organometallic and coordination chemistry of heavier analogs of FcDAC , in particular a redox‐switchable N ‐heterocyclic germylene (NHGe) based on the [3]ferrocenophane ligand arrangement (target, Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…We speculated that the intermetallic communication in these polynuclear scaffolds might be raised by increasing the overall orbital overlap of the constituents. Based on our experience with divalent Group 14 element compounds containing N ‐ligands,– and ligands based on heavier Group 14 elements, we thought to achieve this goal by substituting the carbene C atom in FcDAC with a heavier, divalent Group 14 element, that is, by a donor atom featuring much larger and more diffuse valence orbitals, in particular the π‐acceptor orbital . Therefore, we became interested in exploring the organometallic and coordination chemistry of heavier analogs of FcDAC , in particular a redox‐switchable N ‐heterocyclic germylene (NHGe) based on the [3]ferrocenophane ligand arrangement (target, Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…[4] Landmark examples in case of germanium are the stable germanium vinylidene A by Aldridge [5] and Scheschkewitz's silagermenylidene B (Figure1). [6] However,o ften no multiple bonds but only single or dative bonds are formed [7] such as in Driess' three coordinate [Ge:] 2 + complex D [8] as well as in allene-like structures R 2 E=E=ER 2 , [9] such as germylone C [10] or the di(germylene)-substituted germene E. [11] The most common strategy to access such low-valent compounds is the reduction of halo precursors which upon treatment with strong reducing agents form an ew element-element bond (e.g. to A, B, E).…”
mentioning
confidence: 99%
“…STALKE et al as well as BREHER et al both reported metal complexes with a germanium atom coordinated to three pyrazol molecules via the nitrogen atoms. [84,85,86] These molecules can be described as well as monocationic with a [GeCl 3 ]counterion. With the available data from the x-ray diffraction experiment no definitive answer can be obtained and additional structural information need to be gathered like IR and Raman spectra to identify the true nature of the cocrystallized molecule.…”
Section: Iminophosphorane Ligand Systems In Metal Coordinationmentioning
confidence: 99%